Human colonic in vitro fermentation of water-soluble arabinoxylans from hard and soft wheat alters Bifidobacterium abundance and short-chain fatty acids concentration - Paesani, Candela (2020)
The human intestinal microbiome plays an important role in health due to the large number of beneficial effects related to the bacterial profile and the metabolites generated in the intestine. Arabinoxylans are compounds present in different cereals such as wheat and they can modulate the profile and functioning of some beneficial bacteria from human intestinal microbiota. In the present work, a colonic in vitro fermentation with human faecal inoculum was done using arabinoxylans extracted from Argentinian hard and soft wheat as substrates. Molecular size alteration of arabinoxylans were studied during fermentation and Lactobacillus and Bifidobacterium abundance as well as short chain fatty acids concentrations were determined. The arabinoxylans fermentation was proved to induce the growth of Bifidobacterium and the release of short-chain fatty acids. The speed and efficiency of fermentation were different for each of the arabinoxylan extracted from both wheat genotypes, perhaps because of differences in their chemical and physical structures. The consumption of water-extractable arabinoxylans (WE-AX) (either supplemented or enriched) to maintain the balance or modulate in a favorable way the profile of Bifidobacterium can be an important contribution to the human health.